2014
DOI: 10.1097/iop.0000000000000054
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cicatrization Analysis in Periocular Incisions for Oculoplastic Surgery Performed With Cold Blade and Colorado Needle

Abstract: Esthetic results of periocular scars secondary to skin incisions performed with cold blade or Colorado needle are clinically similar in Spanish patients. Esthetic result of dacryocystorhinostomy scars showed lower scores in OSAS and VSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“… 1 With eyelid incisions usually healing well, and scar hypertrophy and keloids being common on the chest wall, we chose to use paired eyelid and presternal tissues for our study to represent opposite ends of the clinical spectrum of cutaneous scarring. 2 , 3 , 5 Because fibroblasts are the primary drivers of scarring 15 and their biological properties are known to vary with their anatomical origin, 14 , 16 18 , 23 we surmised that the strikingly different scarring behavior observed in eyelid and chest skin could reflect different properties of the local cutaneous fibroblasts. We used our well-characterized in vitro 3D model of tissue contraction 21 , 26 29 to assess the contractile properties of the tissue-derived fibroblasts in classical free-floating collagen gels and further analyzed the intrinsic mechanical properties of the cells within engineered tissues mimicking physiological environments.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“… 1 With eyelid incisions usually healing well, and scar hypertrophy and keloids being common on the chest wall, we chose to use paired eyelid and presternal tissues for our study to represent opposite ends of the clinical spectrum of cutaneous scarring. 2 , 3 , 5 Because fibroblasts are the primary drivers of scarring 15 and their biological properties are known to vary with their anatomical origin, 14 , 16 18 , 23 we surmised that the strikingly different scarring behavior observed in eyelid and chest skin could reflect different properties of the local cutaneous fibroblasts. We used our well-characterized in vitro 3D model of tissue contraction 21 , 26 29 to assess the contractile properties of the tissue-derived fibroblasts in classical free-floating collagen gels and further analyzed the intrinsic mechanical properties of the cells within engineered tissues mimicking physiological environments.…”
Section: Discussionmentioning
confidence: 97%
“…Differences in the resting tensions within, and rigidity of, engineered tissue matrices derived from eyelid and presternal fibroblasts might also belie the traditional belief that differences in clinical scarring are solely related to tissue tension and skin thickness. Indeed, dermal fibroblasts populations are extremely heterogeneous, 14 , 16 18 , 23 and the overall mixed populations that we have isolated may comprise various subsets of fibroblasts and fibroblast-like cells, including mesenchymal stem cells. 33 36 Furthermore, as dermal fibroblasts from the face originate from the neural crest, whereas fibroblasts from the ventral skin are derived from the lateral plate mesoderm, 34 , 35 and we cannot exclude the possibility that the differences we observed between the 2 populations are linked to the different anatomical origins of the cells analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that in later operations, surgeons could incise with electrocautery quicker than during prior operations and sometimes quicker than when using the scalpel. In a systematic review, the authors found five previous studies [17][18][19][20][21] on Colorado needle electrocautery for upper eyelid skin incision; however, among these articles, they did not have an RCT study to compare Colorado needle electrocautery and a scalpel in upper blepharoplasty incision with respect to bleeding during skin incision and scarring using standard evaluation. Moreover, there were no previous studies on Asian people with poor scar outcomes compared with White people.…”
Section: Prs Global Open • 2023mentioning
confidence: 99%
“…Incision scars of the lower eyelid and medial canthus were evaluated by 3 plastic surgeons using the Vancouver scar scale (VSS). 12 The surgeons were blinded to the surgical treatment of each patient and were not participants of this study.…”
Section: Studymentioning
confidence: 99%